Fast and ultra-sensitive voltammetric detection of lead ions by two-dimensional graphitic carbon nitride (g-C3N4) nanolayers as glassy carbon electrode modifier. (February 2019) - Hatamie, Amir; Jalilian, Pouya; Rezvani, Ehsan; Kakavand, Amin; Simchi, Abdolreza
Graphical abstract: Graphitic carbon nitride (g-C3 N4 ) nanosheets were synthesized and used as an efficient electrode modifier for detection of lead ions in environmental samples. Highlights: Graphitic carbon nitride (g-C3 N4 ) monolayers were synthesized and used as an efficient glassy electrode modifier. The proposed sensor could detect lead ions with a limit of detection of 3 ppb. The potential of the modified electrode in fast determination of lead ions in water and soil was shown. Abstract: Recently, graphitic carbon nitride (g-C3 N4 ) has attracted great interest for photo(electro)chemical applications such as sensing, solar energy exploitation, photocatalysis, and hydrogen generation. This paper presents the potential application and benefits of g-C3 N4 nanolayers as a green and highly efficient electrode modifier for the detection of trace lead ions in drinking water and urban dust samples. Carbon nitride nanosheets with a thickness of ∼6 A° and lateral of 100–150 nm were prepared through high-temperature polymerization of melamine followed by sonication-assisted liquid exfoliation. A glassy carbon electrode (GCE) was modified by a thin layer of g-C3 N4 through drop casting and used for fast and sensitive (ppb range) detection of lead ions. It is shown that the g-C3 N4 nanosheets have a total specific area of about 45 m 2 /g, causing an increase in the microscopic surface area of GCE by a factor of 20 in comparison to the bar electrode; hence, enhanced peak current intensity in voltammetric studies is attained. Differential pulse anodic stripping voltammetry indicates two linear anodic stripping responses of 2.4–7.5 ng mL −1 (R 2 = 0.983) and 10.0–1000.0 ng mL −1 (R 2 = 0.993). These ranges fulfill the requirements of the U.S. EPA and WHO standards for the quality control of drinking water. Measurements on urban dusts and drinking water also indicate the potential of the modified electrode for fast and ultrasensitive detection of lead ions in real samples. The advantages and figure of merit of the developed electrode for lead sensing are addressed.